Effect of hydrothermal carbonization on storage process of woody pellets: Pellets' properties and aldehydes/ketones emission. (July 2018) - Li, Hui; Wang, Siyuan; Huang, Zhongliang; Yuan, Xingzhong; Wang, Ziliang; He, Rao; Xi, Yanni; Zhang, Xuan; Tan, Mengjiao; Huang, Jing; Mo, Dan; Li, Changzhu
Graphical abstract: Highlights: The qualities and stability during storage was improved on the hydrochar-pellets. The enhanced aldehydes and ketones emission were found for the hydrochar-pellets. The total emission of aldehydes/ketones was established as the first-order equations. The kind and amount of unsaturated fatty acids in the hydrochar-pellets were enhanced. The unsaturated fatty acids amount was decreased at higher HTC temperature. Abstract: Effect of hydrothermal carbonization (HTC) on the hydrochar pelletization and the aldehydes/ketones emission from pellets during storage was investigated. Pellets made from the hydrochar were stored in sealed apparatuses for sampling. The energy consumption during pelletization and the pellets' properties before/after storage, including dimension, density, moisture content, hardness, aldehyde/ketones emission amount/rate and unsaturated fatty acid amount, were analyzed. Compared with untreated-sawdust-pellets, the hydrochar-pellets required more energy consumption for pelletization, and achieved the improved qualities, resulting in the higher stability degree during storage. The species and amount of unsaturated fatty acids in the hydrochar-pellets were higher than those in the untreated-sawdust-pellets. The unsaturated fatty acids content in the hydrochar-pellets was decreased with increasing HTC temperature. Higher aldehydes/ketones emission amount and rates with a longer emission period were found for the hydrochar-pellets, associated with variations of structure and unsaturated fatty acid composition in pellets.